Incidence of secondary pulmonary hypertension in adults with atrial septal or sinus venosus defects. Issue 1 (1st July 1999) - Vogel, M; Berger, F; Kramer, A; Alexi-Meshkishvili, V; Lange, P E
Abstract : OBJECTIVE: To examine the incidence of raised pulmonary artery pressure and resistance in adults with isolated atrial septal defect within the oval fossa (so called secundum defect) or sinus venosus defect. DESIGN: A historical, retrospective, unrandomised study. SETTING: A tertiary referral centre. METHODS: Cardiac catheterisation was performed in all patients, with measurement of pulmonary artery pressure and resistance. Pulmonary to systemic flow ratio was calculated using the Fick principle. Pulmonary hypertension was defined as mean pulmonary artery pressure > 30 mm Hg, and increased resistance as an Rp/Rs ratio > 0.3. PATIENTS: All patients with a secundum atrial septal or sinus venosus defect who presented between July 1988 and December 1997 were enrolled in the study. RESULTS: Pulmonary artery pressure and resistance in the patients with sinus venosus defect (n = 31) was higher than in patients with atrial septal defect (n = 138). Pulmonary hypertension was present in 26% of patients with sinus venosus and in 9% of patients with atrial septal defect. The incidence of raised pulmonary vascular resistance was 16% in patients with sinus venosus and 4% in patients with atrial septal defect. The increase in resistance occurred at a younger age in sinus venosus defect than in atrial septal defect. CONCLUSIONS: Patients with sinus venosus defect have higher pulmonary pressures and resistances and develop these complications at younger age than patients with atrial septal defects. Thus they should be managed differently than patients with "simple" atrial septal defects.